AB0829 Persistence on golimumab as second line biological therapy in patients with spondyloarthritis (AXIAL SPONDYLOARTHRITIS AND PSORIATIC ARTHRITIS). go-beyond, a retrospective study. (12th June 2018) - González Fernández, C.M.; Alegre-Sancho, J.J.; García-Carazo, S.; Rodríguez-Heredia, J.M.; Bachiller-Corral, J.; Martín López, M.; Retuerto Guerrero, M.; Martín Santos, J.M.; Álvarez-Rivas, N.; Egües Dubuc, C.A.; Villa-Blanco, I.; Laiz, A.; et al.
Abstract : Objectives: In this retrospective study we assess the 1 to 3 year probability of persistence on golimumab in patients with spondyloarthritis (SpA), axial SpA or psoriatic arthritis (PsA) who started treatment with golimumab as second biological (after withdrawal of a first anti TNF-alpha drug) Methods: GO-BEYOND was a retrospective study undergone in 20 Spanish rheumatology clinics. Information was collected on all axial SpA and PsA patients who initiated golimumab between January 2013 and December 2015 as second anti TNF-alpha (i.e. after discontinuation of a first anti TNF-alpha drug). Centres in which all the patients could not be included were excluded from the analysis. The probability of persistence was calculated with a Kaplan-Meier test and comparisons were done with the log-rank test. Results: 210 patients were included (131 with axial SpA and 79 with PsA, mean age 49 years [SD=12], 40% women, median duration of disease at the initiation of golimumab 80.5 months). Reasons for discontinuation of the first anti TNF-alpha were loss of efficacy (71.4%), poor tolerability or adverse event (11.0%) and patient or physician preference (17.6%). During a median follow-up of 29.3 months, 72 of 210 patients (34.3%) discontinued golimumab, due to primary failure (n=21), disease reactivation or secondary failure (n=29), poor tolerability (n=4), adverse events (n=10), inactive disease or patient-physician agreement (n=8). The probability of persistence on golimumab since treatment initiation was 80% at year 1 (95% CI 75–86), 70% at year 2 64 – 77 and 65% at year 3 [59 – 72]. The figures were similar in patients with axial SpA or PsA, and in patients who discontinued the first anti TNF-alpha due to loss of efficacy or to other reasons (p=0.121 and p=0.835, table 1). n=number at risk, SpA=Spondyloarthritis; PsA=Psoriatic arthriitis Conclusions: After discontinuation of a first anti TNF-alpha, patients with spondyloarthritis showed a high probability of persistence on golimumab. The probability of persistence was similarly high in patients with axial SpA or PsA, and in patients who discontinued the first anti TNF-alpha due to loss of efficacy vs other reasons. Real life effectiveness of golimumab as second anti TNF-alpha is high and durable in SpA patients. Acknowledgements: This Study was funded by Merck Sharp and Dohme, Spain Disclosure of Interest: None declared